Real-World Experiences With Facilitated Subcutaneous Immunoglobulin Substitution in Patients With Hypogammaglobulinemia, Using a Three-Step Ramp-Up Schedule - Hustad, Nina B.; Degerud, Hanna M.; Hjelmerud, Ingrid; Fraz, Mai S. A.; Nordøy, Ingvild; Trøseid, Marius; Fevang, Børre; Aukrust, Pål; Jørgensen, Silje F. (Frontiers in Immunology, 2021)
Immunoglobulin replacement therapy with facilitated subcutaneous immunoglobulin (fSCIg) can be self-administrated at home and given at longer intervals compared to subcutaneous immunoglobulin (SCIg) therapy, but real-word experience of home-based fSCIg therapy is limited. Herein we present our real-word clinical experiences with home-based fSCIg therapy using a three-step ramp-up schedule. We registered data from all patients with immunodeficiency starting fSCIg from 01.01.2017 to 31.12.2019. For comparison we also included patients starting conventional SCIg training. Fifty-four patients followed for a median of 18 months (IQR 12, range 0–40), received fSCIg training, and 84 patients received conventional SCIg training. Out of 54 patients starting with fSCIg, 41 patients had previous experience with conventional SCIg therapy, and the main reason for starting fSCIg was ‘longer intervals between therapies’ (n=48). We found an increase in training requirement for fSCIg (3+1 [2-9] days) compared to conventional SCIg (2+0 [1-7] days), P<0.001 (median ± IQR, [range]). For fSCIg training, IgG levels were stable from baseline (8.9±2.3 g/L), 3-6 months (10.2±2.2 g/L) and 9-12 months (9.9±2.3 g/L), P= 0.11 (mean ± SD). The most common side-effect was: ‘rubor around injection site’ (n=48, 89%). No patients experienced severe adverse events (grade 3-4). Thirteen patients (24%) discontinued fSCIg therapy due to local adverse events (n=9), cognitive/psychological difficulties (n=6) and/or systemic adverse events (n=3). In conclusion, fSCIg training using a three-step ramp-up schedule is safe and well tolerated by the majority of patients, but requires longer training time compared to conventional SCIg.